2011
DOI: 10.1097/gme.0b013e31820e9acf
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valerian on sleep quality in postmenopausal women

Abstract: Valerian improves the quality of sleep in women with menopause who are experiencing insomnia. Findings from this study add support to the reported effectiveness of valerian in the clinical management of insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…The 3 most common problems that cause discomfort to women during the postmenopausal period are vasomotor changes, insomnia, and fatigue (Ameratunga, Goldin, & Hickey, 2012;Lai, Chen, Chen, Chen, & Wang, 2006;Timur & Şahin, 2010;Timur & Şahin, 2012). The incidence of insomnia during the menopausal period ranges between 12% and 70% in the literature (Perez, Garcia, Palacios, & Perez, 2009;Simon & Reape, 2009;Singh & Pradhan, 2014;Taavoni, Ekbatani, Kashaniyan, & Haghani, 2011;Terauchi et al, 2010). Perez et al (2009) found that the postmenopausal period has the highest insomnia rate of all periods in human life (49.4%) (Perez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The 3 most common problems that cause discomfort to women during the postmenopausal period are vasomotor changes, insomnia, and fatigue (Ameratunga, Goldin, & Hickey, 2012;Lai, Chen, Chen, Chen, & Wang, 2006;Timur & Şahin, 2010;Timur & Şahin, 2012). The incidence of insomnia during the menopausal period ranges between 12% and 70% in the literature (Perez, Garcia, Palacios, & Perez, 2009;Simon & Reape, 2009;Singh & Pradhan, 2014;Taavoni, Ekbatani, Kashaniyan, & Haghani, 2011;Terauchi et al, 2010). Perez et al (2009) found that the postmenopausal period has the highest insomnia rate of all periods in human life (49.4%) (Perez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that valerian would be effective for improving subjective experiences of insomnia. In addition, valerian was recently given to medical patients with mild sleep problems, such as menopausal women (Taavoni et al, 2011) and cancer patients (Barton et al, 2011).…”
Section: Valerian (Valeriana Officinalis)mentioning
confidence: 99%
“…Taavoni et al 16 compared the valerian and placeboon sleep disorder; 36% of women reported a significant improvement as comparison to only 8% in the placebo group, difference between group were significant.…”
Section: Resultsmentioning
confidence: 99%